Education for intercultural citizenship : concepts and comparisons - Alred, Geof.; Byram, Mike.; Fleming, Mike. (b)
This book examines citizenship education from the perspective of interculturality in order to extend its meaning and significance within and beyond the nation state, and in education in the nation state. There are chapters which deal with theory and concepts and others which present country and international case studies.
Includes references.
Keywords: Citizenship Study and teaching; Citizenship Study and teaching Cross-cultural studies